DNA fingerprinting in plants : (CRC Press, 2005)
Like its successful predecessor, this completely revised new edition serves as a comprehensive introduction to the field, as well as a handy reference for the researcher. Within the context of rapid advances in the field, the new edition focuses on PCR-based fingerprinting, including more sophisticated techniques. The description of the technology is complemented by a significant amount of background information. The new edition provides a complete update of the extensive survey of applications of DNA fingerprinting in plants and a comparison of different types of molecular markers. This second edition is a valuable manual for beginners and active researchers